Establishment of a CRISPR/Cas9 knockout library for screening type I interferon-inducible antiviral effectors in pig cells - Dang, Wen; Li, Tao; Xu, Fan; Wang, Yannan; Yang, Fan; Zheng, Haixue (Frontiers in Immunology, 2022)
Diseases caused by emerging swine viruses had a great economic impact, constituting a new challenge for researchers and practicing veterinarians. Innate immune control of viral pathogen invasion is mediated by interferons (IFNs), resulting in transcriptional elevation of hundreds of IFN-stimulated genes (ISGs). However, the ISG family is vast and species-specific, and despite remarkable advancements in uncovering the breadth of IFN-induced gene expression in mouse and human, it is less characterized with respect to the repertoire of porcine ISGs and their functional annotation. Herein, with the application of RNA-sequencing (RNA-Seq) gene profiling, the breadth of IFN-induced gene expression in the context of type I IFN stimulation was explored by using IBRS-2 cell, a commonly used high-efficient cultivation system for porcine picornaviruses. By establishing inclusion criteria, a total of 359 ISGs were selected. Aiming to identify key effectors mediating type I IFN inhibition of swine viruses, a CRISPR/Cas9 knockout library of 1908 sgRNAs targeting 5’ constitutive exons of 359 ISGs with an average of 5 to 6 sgRNAs per gene was constructed. Using VSV-eGFP (vesicular stomatitis virus, fused with GFP) as a model virus, a subset of highest-ranking candidates were identified, including previously validated anti-VSV genes IRF9, IFITM3, LOC100519082 and REC8, as well as several novel hits. This approach attains a high level of feasibility and reliability, and a high rate of hit identification, providing a forward-looking platform to systematically profile the effectors of type I IFN antiviral response against porcine viruses.